2019
DOI: 10.48550/arxiv.1903.11360
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A General Framework for Endowment Effects in Combinatorial Markets

Abstract: Losses loom larger than gains" -Daniel Kahneman; Amos TverskyThe endowment effect, coined by Nobel Laureate Richard Thaler, posits that people tend to inflate the value of items they own. This bias has been traditionally studied mainly using experimental methodology. Recently, Babaioff et al. proposed a specific formulation of the endowment effect in combinatorial markets, and showed that the existence of Walrasian equilibrium with respect to the endowed valuations extends from gross substitutes to submodular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 22 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…In this section we show that for any valuation profile, every welfare-maximizing allocation can be supported in a 2PE with a discrepancy of at most m. The proof of Proposition B.1 is similar to the proof of Proposition 7.1 in [9].…”
Section: B An Upper Bound On the Discrepancy Of The Optimal Allocationmentioning
confidence: 72%
See 4 more Smart Citations
“…In this section we show that for any valuation profile, every welfare-maximizing allocation can be supported in a 2PE with a discrepancy of at most m. The proof of Proposition B.1 is similar to the proof of Proposition 7.1 in [9].…”
Section: B An Upper Bound On the Discrepancy Of The Optimal Allocationmentioning
confidence: 72%
“…Babaioff et al [1] showed that every market with submodular valuations admits an endowment equilibrium with at least a half of the optimal welfare. Ezra et al [9] introduced a general framework that captures a wide range of formulations for the endowment effect, and showed that stronger endowment effects can lead to existence of endowment equilibrium also in XOS markets. We show conditions under which one can transform an endowment equilibrium to a 2PE and vice versa.…”
Section: Additional Related Workmentioning
confidence: 99%
See 3 more Smart Citations